COMPREHENSION DES TEXTES FRANÇAIS CHEZ LES ELEVES DE DEUXIEME ANNEE DES HUMANITES PEDAGOGIQUES DE QUELQUES ECOLES DE LA COMMUNE KASUKU, VILLE DE KINDU. - Alphonse, Okamba Mundala (IJRDO- Journal of Educational Research, 2022)
The main objective of this research is to evaluate the level of performance of syntactic and morphological entries of words in a text in second year students of pedagogical humanities.The analysis of the data was carried out by calculating the arithmetic mean, standard deviation, median, coefficient of variation, yield, analysis of variance.In a global way, the comprehension of the syntactic and morphological entries for the seen text is sufficient, the output is higher than 50%. For the unseen text, the comprehension of the syntactic and morphological entries is insufficient, the output is lower than 50%.The variable institution of attendance had no effect on performance.To improve the learning of reading instruction, teachers can frequently use the direct method combined with the audio-oral and audio-visual method, the global method. Emphasize comprehension by subjecting learners to the cloze exercise.